Rare earth doped metal oxide nanoparticles for photocatalysis: a perspective - Mehtab, Amir; Ahmed, Jahangeer; Alshehri, Saad M; Mao, Yuanbing; Ahmad, Tokeer (Nanotechnology, 2022)
Metal oxides are well-known materials that have been considered as the prominent photocatalysts. Photocatalysis is a promising way to address the environmental issues which are caused by fossil fuel the combustion and industrial pollutants. Lot of efforts such as doping of metal oxides with metals, non-metals have been made to enhance their photocatalytic activity. More specifically, in this review we have discussed detailed synthesis procedures of rare earth doped metal oxides performed in the past decades. The advantage of doping metal oxides with rare earth metals is that they readily combine with functional groups due to the 4f vacant orbitals. Moreover, doping rare earth metals causes absorbance shift to the visible region of the electromagnetic spectrum which results to show prominent photocatalysis in this region. The effect of rare earth doping on different parameters of metal oxides such as band gap and charge carrier recombination rate has been made in great details. In perspective section, we have given a brief description about how researchers can improve the photocatalytic efficiencies of different metal oxides in coming future. The strategies and outcomes outlined in this review are expected to stimulate the search for a whole new set of rare earth doped metal oxides for efficient photocatalytic applications.